L’affaire Flavy-Choinet, un exemple de résolution des conflits au lendemain de la reconquête de la Normandie par Charles VII - Lydwine Scordia (Tabularia)
The act of May 20, 1464, passed before the tabellion of Rouen, reconstructs a conflict of about half a century (between the time of the Lancastrian monarchy and the after-reconquest of the duchy by Charles VII) between two families, one noble (Flavy) and the other bourgeois (Choinet), about the possession and property of the noble fief of Cliponville (Pays de Caux). The act summarizes the proceedings initiated: “clameur de haro”, trial before the assizes of the bailiff (Caudebec), complaint before the Exchequer, and finally compromise infrajudicial not litigated before the tabellion. It informs on the practices of the Norman Custom at the time of the pacification.